Articulação de saberes teóricos e práticos na promoção do letramento literário no projeto Colmeia Literária - Silva, Thais Almeida da (Universidade Federal do Tocantins, 2020)
In this monograph, we investigated how the reading mediators of the Literary Beehive Project (LBP) articulated the theoretical and practical knowledge in the promotion of literary literacy in Reading Circles (RC) in different sociocultural contexts. The LBP was an extension project idealized in the “Literary Literature” discipline, taught in the Course of Letters / UFT, in the period 2017.2. The proposal of this university extension project is to create a network of readers in different public spaces of municipality of Araguaína (TO), aiming promote the exchange of literary reading experiences between young mediators (literacy agents) and readers of different age groups, through access to literary works. In order to substantiate the research presented, the theoretical assumptions proposed by Abramovich (1998), Candido (2008), Cosson (2014), Street (2014), Soares (2017) and Zilberman (2011) were mobilized. This is a research with a qualitative and interpretative approach, and as to the procedures, it corresponds to a case study. In order to compose the thematic clipping, in this study, data was analyzed concerning the dynamics and didactic organization of the RC meetings in (03) three working groups respectively, denominated “Flor de Lótus" (Lotus Flower), “Flor de Murici” (Murici Flower) and “Flor de Ipê” (Ipê Flower). These groups were chosen according to the singularities of the LBP target readers. In the first, children from a peripheral neighborhood participated; in the second, the participants were elderly of a host institution; and in the third, were people (adults and children) who attended the public walk of Via Lago, place for leisure and sports practice in the city. The corpus of this investigation consists of the researcher's field diary and the academic experience reports. Also included, are photos and audio transcripts (extracted from video) that complement the contextualization of the analyzed data. From the study of the linguistic materialities generated, the following categories of analysis were produced: a) Impacts of the Literary Hive Project on the academic training of literacy agents; b) Contributions of the Beehive Literary Project for the formation of readers in the view of the participants; c) The moment in which the scholars see themselves as agents of literacy. The results pointed out that the entire process of LBP implementation was guided by theoretical and practical implications that led to the didactic actions, as well as the theoretical reflections underlying the activities carried out (elaboration, planning, execution, evaluation).